The need for web development quality to develop high-quality web applications - Abdul Aziz, Azlianor; Emran, Nurul Akmar; Abdullah, Noraswaliza; Sulong, Muhammad Suhaizan (RSIS International, 2024)
In the rapid world of technology, web development faces a complex but significant challenge, particularly in the development of quality web applications. In many cases, end users often assess the quality of web applications based on their error-free performance and user-friendliness as well as enable users to perform tasks quickly anywhere and anytime on any computer devices. Thus, each and every quality issue in the phases of web development process plays a crucial role in the success of a web application and determining the right quality attributes or dimensions can be a challenge. The web development process, carried out in stages based on priorities, presents multiple challenges in communication, management, and teamwork within web development team environments which may adversely impact the overall quality of web applications. This research focuses on the influence of the web development process emphasising quality at each stage of creating high-quality web applications. This will then bring into case studies and quantitative metrics to produce a framework for the web development team to comprehend and adhere to the key quality principles of web application development.